1996
DOI: 10.1152/ajpendo.1996.271.2.e317
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glucocorticoids on energy metabolism and food intake in humans

Abstract: The effect of glucocorticoid administration on energy metabolism and food intake was studied in 20 healthy, nondiabetic Caucasian male volunteers [27 +/- 5 (SD) yr, 72 +/- 9 kg, 20 +/- 7% body fat] randomly and blindly assigned to glucocorticoid (methylprednisolone, METH; n = 10) or placebo (PLAC; n = 10) treatment. Each subject was studied twice: during a weight maintenance diet and during ad libitum food intake. Energy metabolism was measured by indirect calorimetry and food intake by an automated food-selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
274
2
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(290 citation statements)
references
References 22 publications
10
274
2
1
Order By: Relevance
“…(Dagogo-Jack et al, 1997;Miell et al, 1996;Newcomer et al, 1998;Slieker et al, 1996;York, 1996) CRH and Ucn 3 (Bernier, 2006;Ohata and Shibasaki, 2011;Smagin et al, 1998) CART (Kask et al, 2000;Xu et al, 2010) Nesfatin-1 (Goebel et al, 2009;Stengel et al, 2011) NPW (Beck et al, 2010) Melanocortins (Liu et al, 2007;Yamano et al, 2004) central monoaminergic systems (Gibson, 2006) autonomous nervous system (Seematter et al, 2004) Stress induces hyperphagia due to reduction of: sensor specific satiety (Ahn and Phillips, 2012;Ortolani et al, 2011) stressor aversiveness (Piazza and Le Moal, 1997) CRH signaling? (Foster et al, 2009;la Fleur et al, 2005;Pecoraro et al, 2004) due to activation of central reward pathways (Piazza and Le Moal, 1997), due to alterations in gut microbiota (Tehrani et al, 2012) Glucocorticoids induce hyperphagia (Dallman, 1993;Drapeau et al, 2003;Epel et al, 2000;Tataranni et al, 1996) due to increased signaling of: NPY (Gyengesi et al, 2010;Krysiak et al, 1999;McKibbin et al, 1992;White et al, 1994;Wilding et al, 1993), AgRP (Coll et al, 2005;Savontaus et al, 2002), Nociceptin (Green and Devine, 2009;Nativio et al, 2011;…”
Section: Q4mentioning
confidence: 99%
See 1 more Smart Citation
“…(Dagogo-Jack et al, 1997;Miell et al, 1996;Newcomer et al, 1998;Slieker et al, 1996;York, 1996) CRH and Ucn 3 (Bernier, 2006;Ohata and Shibasaki, 2011;Smagin et al, 1998) CART (Kask et al, 2000;Xu et al, 2010) Nesfatin-1 (Goebel et al, 2009;Stengel et al, 2011) NPW (Beck et al, 2010) Melanocortins (Liu et al, 2007;Yamano et al, 2004) central monoaminergic systems (Gibson, 2006) autonomous nervous system (Seematter et al, 2004) Stress induces hyperphagia due to reduction of: sensor specific satiety (Ahn and Phillips, 2012;Ortolani et al, 2011) stressor aversiveness (Piazza and Le Moal, 1997) CRH signaling? (Foster et al, 2009;la Fleur et al, 2005;Pecoraro et al, 2004) due to activation of central reward pathways (Piazza and Le Moal, 1997), due to alterations in gut microbiota (Tehrani et al, 2012) Glucocorticoids induce hyperphagia (Dallman, 1993;Drapeau et al, 2003;Epel et al, 2000;Tataranni et al, 1996) due to increased signaling of: NPY (Gyengesi et al, 2010;Krysiak et al, 1999;McKibbin et al, 1992;White et al, 1994;Wilding et al, 1993), AgRP (Coll et al, 2005;Savontaus et al, 2002), Nociceptin (Green and Devine, 2009;Nativio et al, 2011;…”
Section: Q4mentioning
confidence: 99%
“…Appetite in humans and animals follows changes in adrenal steroid levels. Anorexia and weight loss are hallmarks of adrenal insufficiency in Addison's disease, whereas increased appetite correlates with GC overproduction in Cushing's syndrome and with exogenous GC administration in normal volunteers (Tataranni et al, 1996). In women experimental stressinduced cortisol secretion increased appetite and craving for sugar (Epel et al, 2000).…”
Section: Central Orexigenic Effectsmentioning
confidence: 99%
“…We have suggested that AMPK is involved in the central and peripheral effects of glucocorticoids. Glucocorticoids activate hypothalamic AMPK activity in vivo (Christ-Crain et al 2008) either directly or via stimulation of endocannabinoid synthesis (Di et al 2005, Christ-Crain et al 2008, and these effects could lead to appetite stimulation (Tataranni et al 1996). In the periphery, glucocorticoids inhibit AMPK activity in adipose tissue, leading to increased lipogenesis and fat storage (Christ-Crain et al 2008).…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…GCTC-induced insulin resistance results in decreased insulin-stimulated glucose uptake in muscle [6], and increased plasma concentrations of NEFA, insulin and leptin [7,8], with troglitazone antagonising this effect [7]. At the whole body level, increased GCTC concentrations are known to increase oxygen consumption [9][10][11], and decrease food intake [12,13] resulting in a more negative energy balance than in pair-fed animals. We have shown that there is a decreased efficiency of oxidative phosphorylation in the liver mitochondria of dexamethasone treated rats [13].…”
mentioning
confidence: 99%